2019
DOI: 10.3390/cli7060084
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Agulhas Eddies on Absorption and Transport of Anthropogenic Carbon in the South Atlantic Ocean

Abstract: The South Atlantic Ocean is currently undergoing significant alterations due to climate change. This region is important to the global carbon cycle, but marine carbon data are scarce in this basin. Additionally, this region is influenced by Agulhas eddies. However, their effects on ocean biogeochemistry are not yet fully understood. Thus, we aimed to model the carbonate parameters in this region and investigate the anthropogenic carbon (Cant) content in 13 eddies shed by the Agulhas retroflection. We used in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Mesoscale eddies, characterised by radii on the order of 100 km and lifetimes of weeks to years, are ubiquitous in the global oceans (Chelton et al, 2011;Pegliasco et al, 2022). Eddies modify the physical (Laxenaire et al, 2019;Nencioli et al, 2018), biological (Carvalho et al, 2019;Dufois et al, 2016;Lehahn et al, 2011;Roughan et al, 2017), and chemical (Arhan et al, 2011;Chen et al, 2007;Orselli, Goyet, et al, 2019; characteristics of the ocean compared to the surrounding waters and can be advected far away from their origin.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale eddies, characterised by radii on the order of 100 km and lifetimes of weeks to years, are ubiquitous in the global oceans (Chelton et al, 2011;Pegliasco et al, 2022). Eddies modify the physical (Laxenaire et al, 2019;Nencioli et al, 2018), biological (Carvalho et al, 2019;Dufois et al, 2016;Lehahn et al, 2011;Roughan et al, 2017), and chemical (Arhan et al, 2011;Chen et al, 2007;Orselli, Goyet, et al, 2019; characteristics of the ocean compared to the surrounding waters and can be advected far away from their origin.…”
Section: Introductionmentioning
confidence: 99%
“…A decay of the Agulhas rings toward the west was evident from SLA (Carvalho et al, 2019;Orselli et al, 2019). Each eddy proved to be different, with different physical and chemical characteristics and different species' presence.…”
Section: Discussionmentioning
confidence: 92%
“…The youngest eddy, E1, was the most discrepant, having the highest vorticity, more nutrients, and a greater density of organisms, and was the only eddy with STMW14. Orselli et al (2019) represented the formation of the eddies of the present study in a video, in which it is possible to observe the start of the formation of E1 with a high SLA. Carvalho et al (2019) suggested that E1, located in the South Atlantic Ocean's eastern basin, represented a younger and stronger structure and a more diverse phytoplankton community (HPLC pigments analysis) than E3 and E5.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations